2011
DOI: 10.1007/s12471-011-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Failure of epicardial pacing leads in congenital heart disease: not uncommon and difficult to predict

Abstract: Aims We evaluate the incidence of epicardial lead failure and try to identify risk factors in patients with congenital heart disease. Methods All patients with a congenital heart defect and an epicardial pacing system, implanted within a timeframe of 25 years, were included in this study. Patients' medical records and lead data were reviewed. Lead failure was defined as the primary endpoint. Results In total 198 active epicardial leads (atrial 40, ventricular 158) were implanted in 93 patients (median age at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…Lead failure in epicardial leads is reported from 8% to 36% with a wide range between centers [ 4 - 7 ]. As stated by Post et al, who reviewed data of 93 patients with congenital heart disease in a single center focussing on possible risk factors for lead failure, only young age at implantation proved to be a risk factor for lead dysfunction [ 8 ]. Interestingly, Murayma et al found congenital heart disease itself to be the only predictor of lead failure in their collective of 109 pediatric patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lead failure in epicardial leads is reported from 8% to 36% with a wide range between centers [ 4 - 7 ]. As stated by Post et al, who reviewed data of 93 patients with congenital heart disease in a single center focussing on possible risk factors for lead failure, only young age at implantation proved to be a risk factor for lead dysfunction [ 8 ]. Interestingly, Murayma et al found congenital heart disease itself to be the only predictor of lead failure in their collective of 109 pediatric patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 10 patients (59%) needed a lead replacement due to lead fracture (35%), lead failure due to high pacing thresholds (12%), or during an elective procedure (upgrade to dual‐chamber device; 12%). Reoperations are an inevitable problem associated with pediatric pacemaker therapy and a very important predictor for lead problems is the age of the patients at implantation of the leads, which was very young in our population. Compared to a study in 93 patients with congenital heart disease having epicardial leads, we found a higher percentage of lead failures, but the median time period before failure was comparable.…”
Section: Discussionmentioning
confidence: 96%
“…Reoperations are an inevitable problem associated with pediatric pacemaker therapy and a very important predictor for lead problems is the age of the patients at implantation of the leads, which was very young in our population. Compared to a study in 93 patients with congenital heart disease having epicardial leads, we found a higher percentage of lead failures, but the median time period before failure was comparable. In comparison to a retrospective study looking at long‐term outcome of epicardial leads, 38% had a lead problem after 5 years, which is a lower percentage than in our findings .…”
Section: Discussionmentioning
confidence: 96%
“…Epicardial leads have a higher rate of lead failure, which can be difficult to predict. [7][8][9][10] At the time of the last surgery in the present case, the patient's RV lead was a 10-year old unipolar epicardial lead. This case highlights the difficult decisions faced during device revision-does one use suboptimal existing leads and risk future lead failure or attempt the implantation of a new lead with all the attendant morbidity of the extra lead implant procedure?…”
mentioning
confidence: 93%